ANALISIS PERTUMBUHAN EKONOMI IKNLUSIF PROVINSI NUSA TENGGARA TIMUR TAHUN 2016-2020 - Lestari, Farida Ayu; Ballo, Fransina W; Kiak, Novi Theresia (Universitas Nusa Cendana, 2023)
This study aims to determine the value of inclusive economic growth and what This study aims to determine the value of inclusive economic growth and what factors influence inclusive economic growth in East Nusa Tenggara districts/cities in 2016-2020. This study uses primary data with PEGR (Poverty Equivalent Growth Rate) method analysis to determine the value of inclusive growth and uses paht analysis to determine the factors that influence inclusive growth. Theresults of the analysis to show the value of inclusive growth from 21 districts and 1 city that experienced inclusive economic growth resulted in the finding that on average in 2016-2020 inclusive growth has increased every year so that in 2020 it experienced the highest achievement with an average of 0.64 which resulted in 21 districts and 1 city of East Nusa Tenggara having reached an inclusive state. Furthermore, to find out what factors affect inclusive economic growth using path analysis / (path analysis) from the test results to know the factors that directly and indirectly influence inclusive economic growth, the level of unemployment on inclusive economic growth and other factors. such as the poverty rate and the gini ratio influence indirectly through economic growth as an intervening variable. The creation of inclusive growth does not only affect economic growth in the poverty rate, unemployment rate and gini ratio so as to accelerate the realization of inclusive growth in East Nusa Tenggara.